Appetite measures as correlates of clinical response in mood disorders treated with ketamine: systematic review - Słupski, Jakub; Mechlińska, Agnieszka; Włodarczyk, Adam; Kwaśny, Aleksander; Szarmach, Joanna; Słupska, Anita; Cubała, Wiesław Jerzy (Frontiers in Nutrition, 2025)
Mood disorders, including major depressive disorder (MDD) and bipolar disorder (BP), significantly impact global health, with MDD affecting over 300 million people and BP affecting approximately 2% of the world’s population. Ketamine, originally an anesthetic, has emerged as a promising treatment for patients with treatment-resistant depression (TRD), due to its unique pharmacological properties, such as N-methyl-D-aspartate (NMDA) receptor antagonism and anti-inflammatory effects. The potential of ketamine in treating depression has sparked debate regarding its effects on appetite. This paper aims to conduct a systematic review focusing on the complex interplay between ketamine treatment and appetite. A total of 78 references were identified from electronic databases: PubMed, Web of Science, APA PsycINFO, and EBSCOhost, with 5 meeting the inclusion criteria for this review, encompassing 678 participants. Appetite was assessed using both clinician-rated and self-reported scales. Two studies reported significant improvement in reduced appetite following ketamine or esketamine treatment; one reported no significant change; one found a paradoxical worsening of reduced appetite; and one noted minimal effect on increased appetite and atypical symptoms. The data presented suggest that in patients with treatment-resistant mood disorders, ketamine may contribute to the improvement of depressive symptoms, including those related to appetite, or may exhibit neutral effects on food consumption desire. Appetite measurement may be a valuable indicator of the antidepressant effect, facilitating signal detection for substances beyond traditional monoaminergic antidepressants. Despite limited data, establishing a confirmed link between appetite and antidepressants could aid in treatment planning, particularly for patients with metabolic disorders or those at risk of malnutrition, potentially improving adherence and outcomes in treatment-resistant mood disorders.Systematic review registrationhttps://www.crd.york.ac.uk/PROSPERO/view/CRD42024510640, identifier CRD42024588790.